Students’ Awareness and Usage of Koha – Online Public Access Catalog (OPAC) (British Journal of Multidisciplinary and Advanced Studies, 2025)
The outbreak of the Covid-19 pandemic made a big impact towards the libraries. As face-to-face mode was constricted, the online digital marketing strategies became a tool to bridge the gap between the library and users through the promotion of online library services and resources. The study was conducted to determine the influence of students’ assessment of online library services and utilization of digital marketing strategies on their online engagements. There were 820 Senior High School students who participated in the study. The study utilized the descriptive-correlational design and data were analyzed using descriptive and inferential statistics. Online survey questionnaires were used for data collection. Findings reveal that students’ assessment of the online library services and extent of utilization of digital marketing strategies were generally high. The students’ engagement towards online library services in terms of affective and cognitive domains were high, in contrast to the behavior domain assessed as moderate. The study found that the students’ online library engagement was influenced by their assessment of online library services and their extent of utilization of digital marketing strategies. It is recommended that the librarians may assess each of the online library services to determine the satisfaction level of the students towards the services as well as continue to improve their services. The library personnel may also consider evaluating their library website as well as using other digital marketing strategies such as Email marketing and SMS mobile marketing or creating more official online accounts to LinkedIn, Viber, Snapshot, Pinterest, and TikTok to further promote their online library services and resources as well as to reach users and non-users of the library.